Adhesive composition for laminating electromagnetic steel sheets

CN117580925BActive Publication Date: 2026-10-27SIKA JAPAN LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202280044158.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-06-21
Filing Date
2022-04-28
Publication Date
2026-10-27
Estimated Expiration
2042-04-28

AI Technical Summary

Benefits of technology

[0060]本发明的电磁钢板层叠用粘接剂组合物,从被适用于电磁钢板起直至制造铁心(层叠铁心)之前为止具有优异的非粘性、即使长期保管至上述制造之前为止、粘接性能也优异、所得到的粘接剂固化物在宽的温度范围韧性优异。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0004619938160000091
    Figure BDA0004619938160000091
Patent Text Reader

Abstract

The present invention aims to provide an electromagnetic steel sheet lamination adhesive composition having excellent non-stickiness until the production of a laminated electromagnetic steel sheet, excellent adhesion even after long-term storage, and excellent toughness of the obtained adhesive cured product in a wide temperature range. The present invention is an electromagnetic steel sheet lamination adhesive composition comprising: an epoxy resin (AA) containing an epoxy resin (A) having three or more epoxy groups in one molecule, the epoxy resin (A) containing an epoxy resin having a softening temperature of 60°C or higher; a phenoxy resin (B) having a glass transition temperature in an uncured state exceeding 120°C as determined by differential scanning calorimetry; and an amine-based latent curing agent (C), the content of the phenoxy resin (B) being 20 to 80 parts by mass relative to 100 parts by mass of the epoxy resin (AA), and the glass transition temperature of the obtained adhesive cured product exceeding 160°C as determined by differential scanning calorimetry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to adhesive compositions for laminating electromagnetic steel sheets. Background Technology

[0002] Traditionally, stators or rotors of electric motors, generators, transformers, etc., have used laminated iron cores. Laminated iron cores typically utilize adhesive compositions to bond and stack multiple layers of electromagnetic steel sheets.

[0003] For laminated cores, for example, Patent Document 1 discloses that the adhesive layer of the laminated electromagnetic steel sheet contains an organic resin (such as epoxy resin) with a glass transition temperature or softening temperature of 50°C to 150°C.

[0004] Patent Document 2 discloses a method for manufacturing annular laminated core material and annular laminated core material. When manufacturing an aramid paper laminated sheet for use as an insulating sheet for the laminated core material, a resin composition comprising an epoxy resin and a polyamide resin is used as an adhesive.

[0005] Patent document 3 discloses a method for manufacturing an adhesive-type laminated core by bonding multiple laminated core sheets together using an adhesive. It specifies that, as an indicator of the heat resistance of the adhesive, the tensile strength is preferably 30 MPa or more after being held at 300°C for 1 hour in a nitrogen atmosphere.

[0006] Patent Document 4 discloses a non-directional electromagnetic steel plate composition for use in rotors, stators, transformers, etc. of electric motors and their manufacturing methods. The non-directional electromagnetic steel plate composition includes a first composition containing a water-soluble epoxy resin and inorganic nanoparticles that are SiO2, TiO2, ZnO, or combinations thereof, and an inorganic additive that is phosphoric acid (H3PO4), sodium hydroxide (NaOH), or combinations thereof. The inorganic nanoparticles are substituted with terminal substituents of the water-soluble epoxy resin, and the epoxy resin is a multifunctional epoxy resin with three or more epoxy groups.

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Application Publication No. 2002-146492

[0010] Patent Document 2: Japanese Patent Application Publication No. 2020-171171

[0011] Patent Document 3: Japanese Patent Application Publication No. 2004-42345

[0012] Patent Document 4: Japanese Patent Publication No. 2016-540901 Summary of the Invention

[0013] The problem the invention aims to solve

[0014] To ensure high performance of the laminated core under operating conditions, as shown in Patent Document 3, the cured product (adhesive cured product) obtained from the adhesive composition for laminated electromagnetic steel sheets is required to have excellent toughness. In particular, recent years have demanded high yield stress over a wide temperature range, including high temperatures (e.g., above 120°C), to improve the toughness of the adhesive cured product. Specifically, for example, a yield stress of 60 MPa or more measured at 25°C and a yield stress of 20 MPa or more measured at 140°C are required.

[0015] However, it is extremely difficult to obtain such a tough cured adhesive from conventional adhesive compositions.

[0016] Next, in the manufacture of the laminated iron core, when using an electromagnetic steel sheet with an adhesive composition, it is required that the adhesive be non-sticky.

[0017] Electromagnetic steel sheets typically using adhesive compositions are first coated with the adhesive composition on their surface and dried. They are then transported or stored in a state where the sheets are overlapped (e.g., in a rolled-up state). If the adhesive is sticky in this state, it will adhere to other electromagnetic steel sheets during transport or storage. When the rolled-up sheet is unrolled for use, the adhesive may peel off from the sheets it should be bonded to. Furthermore, during the die-cutting process, the adhesive composition on the electromagnetic steel sheet may adhere to the die-cutting device, etc.

[0018] Therefore, when the electromagnetic steel sheets are only stacked (before they are finally bonded together to form the stacked electromagnetic steel sheets), the adhesive composition applied to the electromagnetic steel sheets needs to have excellent tack-free properties.

[0019] Furthermore, the adhesive composition for laminated electromagnetic steel sheets is required to maintain its bonding performance even after long-term storage (the bonding performance after long-term storage is excellent).

[0020] In the above case, the inventors, referring to Patent Documents 1 and 2, evaluated the cured product obtained from a composition containing a bisphenol A type epoxy resin and a conventional phenoxy resin. The results showed that the glass transition temperature (heat resistance) of the cured product was not improved, and the non-stickiness of the applied adhesive composition, the high-temperature toughness of the cured adhesive product, and the maintenance of the adhesive performance after long-term storage were insufficient.

[0021] Furthermore, it is known that when the phenoxy resin and epoxy resin mentioned above are changed, and only the Tg (heat resistance) of the obtained adhesive cured product is increased, the yield stress (toughness) of the cured product is not increased, and the non-stickiness of the applied adhesive composition is not improved (Comparative Example 1).

[0022] Next, the epoxy resin was changed to an epoxy resin with a softening temperature of 50°C to 150°C and / or an epoxy resin with more than 3 functions. As a result, the Tg (heat resistance) of the obtained adhesive cured product was increased and the yield stress at room temperature was increased. However, that was all. The toughness of the adhesive cured product under high temperature conditions and the maintenance of the adhesive performance after long-term storage were not sufficient (Comparative Examples 3 and 5).

[0023] Therefore, the purpose of this application is to provide an adhesive composition for laminating electromagnetic steel sheets that has excellent non-adhesiveness up to the point of fabrication of the laminated electromagnetic steel sheets, excellent adhesive performance even after long-term storage, and excellent toughness of the cured adhesive over a wide temperature range.

[0024] Solution for solving the problem

[0025] In order to solve the above-mentioned problems, the inventors conducted repeated and in-depth research and found that the adhesive composition contains an epoxy resin (A) with three or more functions, a phenoxy resin (B) with a glass transition temperature exceeding 120°C in the uncured state, and an amine-based latent curing agent (C). The epoxy resin (A) contains an epoxy resin with a softening temperature of 60°C or higher, and the content of the phenoxy resin (B) is a specific amount. The resulting cured adhesive has a glass transition temperature exceeding 160°C, thereby achieving the desired effect and completing the present invention. [1]

[0027] An adhesive composition for laminating electromagnetic steel sheets comprises: an epoxy resin (AA) containing an epoxy resin (A) having three or more epoxy groups in one molecule.

[0028] Phthaloresin (B) with a glass transition temperature exceeding 120°C in the uncured state, determined by differential scanning calorimetry, and

[0029] Amine-based latent curing agent (C),

[0030] The epoxy resin (A) mentioned above contains epoxy resin with a softening temperature of 60°C or higher.

[0031] The content of the above-mentioned phenoxy resin (B) is 20 to 80 parts by weight relative to 100 parts by weight of the above-mentioned epoxy resin (AA).

[0032] The glass transition temperature of the obtained cured adhesive exceeded 160°C, as determined by differential scanning calorimetry. [2]

[0034] According to the adhesive composition for laminating electromagnetic steel sheets as described in [1], the phenoxy resin (B) contains at least one selected from the group consisting of phosphorus-containing phenoxy resin (B1), fluorene-containing phenoxy resin (B2), and bisphenol S-containing phenoxy resin (B3). [3]

[0036] According to the adhesive composition for laminating electromagnetic steel sheets as described in [1] or [2], wherein the epoxy resin with a softening temperature of 60°C or higher contains phenolic varnish type epoxy resin (A1) and / or cresol varnish type epoxy resin (A2). [4]

[0038] The adhesive composition for laminating electromagnetic steel sheets according to any one of [1] to [3], wherein the content of the epoxy resin with a softening temperature of 60°C or higher is 50% by mass or more of the total amount of the epoxy resin (AA). [5]

[0040] The adhesive composition for laminating electromagnetic steel sheets according to any one of [1] to [4], wherein the epoxy resin (A) further contains an epoxy resin having N,N-diglycidylamino groups, and the content of the epoxy resin having N,N-diglycidylamino groups is 50% by mass or less of the total amount of the epoxy resin (AA). [6]

[0042] According to the adhesive composition for laminating electromagnetic steel sheets as described in [5], wherein the epoxy resin having N,N-diglycidylamino contains epoxy resin (A3) of formula (1) described later and / or epoxy resin (A4) of formula (2) described later. [7]

[0044] The adhesive composition for laminating electromagnetic steel sheets according to any one of [1] to [6], wherein the content of the amine-based latent curing agent (C) is 5 to 70 parts by weight relative to 100 parts by weight of the epoxy resin (AA). [8]

[0046] The adhesive composition for laminating electromagnetic steel sheets according to any one of [1] to [7] further contains a toughening agent (D). [9]

[0048] According to the adhesive composition for laminating electromagnetic steel sheets as described in [8], the toughening agent (D) has an average particle size of 0.005 to 0.6 μm and contains a core-shell type toughening agent (D1).

[10]

[0050] According to the adhesive composition for laminating electromagnetic steel sheets as described in [8] or [9], the content of the toughening agent (D) is 1 to 30 parts by weight relative to 100 parts by weight of the epoxy resin (AA).

[11]

[0052] The adhesive composition for laminating electromagnetic steel sheets according to any one of [1] to

[10] , wherein the content of the difunctional epoxy resin is 0 to 40% by mass of the epoxy resin (AA) described above.

[12]

[0054] The adhesive composition for laminating electromagnetic steel sheets according to any one of [1] to

[11] , wherein the cured adhesive has a yield stress of 60 MPa or more at 25°C as measured according to JIS K7161, and a yield stress of 20 MPa or more at 140°C.

[13]

[0056] A core is formed by alternating layers of electromagnetic steel plates and adhesive layers, wherein the adhesive layers are formed using any one of the electromagnetic steel plate lamination adhesive compositions described in [1] to

[12] .

[14]

[0058] According to the core described in

[13] , the adhesive layer has a yield stress of 60 MPa or more at 25°C as measured according to JIS K7161, and a yield stress of 20 MPa or more at 140°C.

[0059] The effects of the invention

[0060] The adhesive composition for laminated electromagnetic steel sheets of the present invention has excellent non-stick properties from the time it is applied to the electromagnetic steel sheet until the manufacture of the core (laminated core), and its adhesive properties are excellent even after long-term storage until the aforementioned manufacture. The resulting cured adhesive exhibits excellent toughness over a wide temperature range.

[0061] The core formed using the adhesive composition for laminating electromagnetic steel sheets of the present invention exhibits excellent bonding performance and excellent toughness over a wide temperature range. Detailed Implementation

[0062] The embodiments of the present invention will be described in detail below. However, the description of the constituent conditions described below is only one example of the embodiments of the present invention, and the present invention is not limited by the following content as long as its spirit is not changed.

[0063] In this specification, when the expression “~” is used, it is used as an expression that includes the numerical values ​​before and after it.

[0064] Unless otherwise specified, the manufacturing methods for the components described in this specification are not particularly limited. Examples of methods known in the past can be cited.

[0065] In this specification, when referring to the adhesive composition for laminating electromagnetic steel sheets of the present invention, the statement that at least one of the above-mentioned non-adhesiveness, adhesive properties, and toughness is superior is sometimes used to describe "the effect of the present invention is superior". The same applies to the case where at least one of the adhesive properties and toughness is superior when forming an iron core using the adhesive composition for laminating electromagnetic steel sheets of the present invention.

[0066] [Adhesive composition for laminating electromagnetic steel sheets]

[0067] The adhesive composition for laminating electromagnetic steel sheets of the present invention (the composition of the present invention) comprises: an epoxy resin (AA) containing an epoxy resin (A) having three or more epoxy groups in one molecule, a phenoxy resin (B) having a glass transition temperature (Tg) of more than 120°C in the uncured state as determined by differential scanning calorimetry (DSC), and an amine-based latent curing agent (C). The epoxy resin (A) contains an epoxy resin with a softening temperature of 60°C or higher, and the content of the phenoxy resin (B) is 20 to 80 parts by mass relative to 100 parts by mass of the epoxy resin (AA). The Tg of the obtained cured adhesive, determined by differential scanning calorimetry, exceeds 160°C.

[0068] It has been found that the compositions of the present invention, by containing not only an epoxy resin with a softening temperature of 60°C or higher, but also a phenoxy resin (B) with excellent cohesive strength, i.e., a Tg exceeding 120°C, result in adhesive cured products that exhibit excellent yield stress not only at 25°C, but also over a wide temperature range including high temperatures. These features are considered the most significant characteristics of the compositions of the present invention.

[0069] The components contained in the composition of the present invention will be described in detail below.

[0070] <<Epoxy Resin (AA)>>

[0071] The compositions of the present invention contain epoxy resin (AA). Epoxy resin (AA) is a compound having multiple epoxy groups.

[0072] The composition of the present invention, by containing epoxy resin (AA), can maintain high bonding reliability for electromagnetic steel sheets.

[0073] It should be noted that in this invention, the epoxy resin (AA) does not contain the phenoxy resin (B) described later, nor does it contain the toughening agent (D) described later.

[0074] • Epoxy equivalent of epoxy resin (AA)

[0075] From the viewpoint that the present invention has superior effects, the epoxy equivalent of the epoxy resin (AA) is preferably 1000 g / eq or less, more preferably 100 to 500 g / eq.

[0076] In this invention, the epoxy equivalent of the epoxy resin can be determined as follows: according to JIS K 7236 standard, using an automatic potentiometric titration apparatus (manufactured by Hiranuma Sangyo Co., Ltd., COM-1600ST), chloroform is used as the solvent, tetraethylammonium bromide acetic acid solution is added, and titration is performed using a 0.1 mol / L perchloric acid-acetic acid solution, thereby determining the epoxy equivalent of the epoxy resin.

[0077] • Molecular weight of epoxy resin (AA)

[0078] From the viewpoint that the present invention has superior effects, the molecular weight of the epoxy resin (AA) is preferably 100 or more and less than 5000.

[0079] The molecular weight of epoxy resin (AA) can be calculated from the epoxy equivalent and the number of epoxy groups in the epoxy resin (AA).

[0080] <Epoxy Resin (A)>

[0081] Epoxy resin (AA) contains epoxy resin (A) having more than 3 epoxy groups in one molecule.

[0082] The number of epoxy groups in one molecule of epoxy resin (A) can be set to 20 or less, but from the viewpoint of better performance of the present invention, it is preferred to have 3 to 12.

[0083] • Content of epoxy resin (A)

[0084] From the viewpoint of achieving superior effects of the present invention, the content of epoxy resin (A) is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more in epoxy resin (AA). When it is less than 50% by mass, the Tg of the cured product cannot be sufficiently increased, resulting in residual problems regarding heat resistance.

[0085] <Epoxy resin with a softening temperature above 60℃>

[0086] In the composition of the present invention, the epoxy resin (A) contains an epoxy resin with a softening temperature of 60°C or higher.

[0087] The composition of the present invention contains an epoxy resin with a softening temperature of 60°C or higher, and exhibits excellent non-stickiness, adhesive properties, and toughness.

[0088] It should be noted that the epoxy resins with a softening temperature of 60°C or higher mentioned above belong to epoxy resin (A), and therefore have more than 3 epoxy groups in one molecule. Sometimes, the epoxy resins with a softening temperature of 60°C or higher mentioned above are referred to as "solid epoxy resins".

[0089] Softening temperature

[0090] In this invention, the softening temperature of the aforementioned solid epoxy resin is 60°C or higher. From the viewpoint of further enhancing the effects of this invention, a softening temperature of 60–110°C is preferred. Above 110°C, the adhesive's coatability on the steel sheet deteriorates, and the adhesive strength may decrease. Furthermore, from the viewpoint of further enhancing the effects of this invention, the aforementioned solid epoxy resin preferably contains an epoxy resin with a softening temperature of 60–80°C and / or an epoxy resin with a softening temperature exceeding 80°C but below 110°C.

[0091] In this invention, the softening temperature of the epoxy resin can be determined according to JIS K7206:2016.

[0092] From the viewpoint that the present invention has superior effects, the above-mentioned solid epoxy resin preferably contains phenolic varnish type epoxy resin (A1) and / or cresol varnish type epoxy resin (A2), more preferably contains epoxy resin (A1) and epoxy resin (A2).

[0093] Phenolic resin varnish type epoxy resin (A1)

[0094] Phenolic varnish-type epoxy resins generally refer to the reaction products of phenolic varnish resins and epichlorohydrin. Examples of phenolic varnish-type epoxy resins (A1) include compounds represented by the following formula (6).

[0095]

[0096] In equation (6), n is 1 or more, and can be 18 or less. From the viewpoint that the present invention has better effects, n is preferably 1 to 10.

[0097] • Cresol-phenolic varnish type epoxy resin (A2)

[0098] Cresol varnish-type epoxy resins generally refer to the reaction products of cresol varnish resins and epichlorohydrin. As a cresol varnish-type epoxy resin (A2), examples of the reaction products of cresol varnish resins and epichlorohydrin shown in the following formula (7) can be cited.

[0099]

[0100] In equation (7), n is 1 or more, and can be 18 or less. From the viewpoint that the present invention has better effects, n is preferably 1 to 10.

[0101] • Content of solid epoxy resin

[0102] The content of the aforementioned solid epoxy resin (the total content when the solid epoxy resin contains both epoxy resin (A1) and epoxy resin (A2)) is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, of the total amount of the aforementioned epoxy resin (AA) from the viewpoint of achieving better results for the present invention (especially better non-adhesiveness and less likelihood of the electromagnetic steel plates sticking together). If the content is less than 50% by mass, sufficient non-adhesiveness cannot be obtained, and the steel plates may stick together during storage.

[0103] Epoxy resins containing nitrogen atoms

[0104] From the viewpoint that the present invention has superior effects, the epoxy resin (A) described above preferably further contains an epoxy resin having nitrogen atoms (also known as a nitrogen-containing epoxy resin), and more preferably contains an epoxy resin having N,N-diglycidylamino (the following structure).

[0105] It should be noted that nitrogen-containing epoxy resins do not include epoxy resins with a softening temperature above 60°C.

[0106]

[0107] In the above structural formula, * represents the bonding position.

[0108] The epoxy resin having N,N-diglycidylamino group (also known as epoxy resin containing glycidylamino group) preferably has 1 to 2 N,N-diglycidylamino groups in one molecule.

[0109] The epoxy resins containing glycidyl amino groups mentioned above may also have epoxy groups other than N,N-diglycidylamino groups (such as glycidyl group, glycidyloxy group, etc.).

[0110] In the case that the above-mentioned epoxy resin containing glycidyl amino groups has one N,N-diglycidyl amino group in one molecule, it may also have epoxy groups other than N,N-diglycidyl amino groups.

[0111] In nitrogen-containing epoxy resins, groups having an epoxy group such as N,N-diglycidylamino can be bonded to linking groups with a valence of 2 or higher. There are no particular limitations on the linking groups. Examples include hydrocarbon groups, preferably hydrocarbon groups having an aromatic hydrocarbon group.

[0112] · Epoxy resin (A3), (A4)

[0113] From the viewpoint of achieving superior effects, the above-mentioned epoxy resin containing glycidyl amino groups preferably contains epoxy resin (A3) as shown in formula (1) and / or epoxy resin (A4) as shown in formula (2), and more preferably contains at least epoxy resin (A4). When the above-mentioned epoxy resin containing glycidyl amino groups contains epoxy resin (A4), it may also contain the above-mentioned epoxy resin (A3).

[0114]

[0115] The nitrogen-containing epoxy resin is preferably in liquid form at room temperature (25°C).

[0116] It should be noted that the nitrogen-containing epoxy resins mentioned above belong to epoxy resin (A), and therefore have more than 3 epoxy groups in one molecule.

[0117] • Content of epoxy resins containing nitrogen atoms

[0118] The content of the nitrogen-containing epoxy resin (the total content of the nitrogen-containing epoxy resin when it contains the above-mentioned epoxy resin (A3) and the above-mentioned epoxy resin (A4)) is preferably 50% by mass or less, more preferably 10 to 40% by mass, and even more preferably 20 to 30% by mass of the total amount of the above-mentioned epoxy resin (AA).

[0119] From the viewpoint of achieving superior effects of the present invention, the content of the epoxy resin (A4) is preferably 10 to 40% by mass of the total amount of the epoxy resin (AA). When it is less than 10% by mass, sufficient heat resistance cannot be obtained, and when it exceeds 40% by mass, sufficient non-stickiness may not be obtained.

[0120] From the viewpoint that the present invention has superior effects, the content of the epoxy resin (A3) is preferably 0 to 20% by mass of the total amount of the epoxy resin (AA).

[0121] Epoxy resins other than epoxy resin (A)

[0122] The aforementioned epoxy resin (AA) may also contain epoxy resins other than epoxy resin (A) having three or more epoxy groups in one molecule (other epoxy compounds).

[0123] Other epoxy compounds mentioned above include, for example, monofunctional epoxy compounds having one epoxy group in one molecule, and difunctional epoxy resins (epoxy resins having two epoxy groups in one molecule).

[0124] Examples of the aforementioned difunctional epoxy resins include bisphenol-type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, brominated bisphenol A type epoxy resin, hydrogenated bisphenol A type epoxy resin, bisphenol S type epoxy resin, and bisphenol AF type epoxy resin; and biphenyl-type epoxy resins, which contain biphenyl groups.

[0125] When the composition of the present invention also contains other epoxy compounds, it preferably contains a difunctional epoxy resin, and more preferably a bisphenol A type epoxy resin.

[0126] • Content of other epoxy compounds

[0127] From the viewpoint that the present invention has superior effects (especially non-stickiness), the content of other epoxy compounds is preferably 0 to 40% by mass of epoxy resin (AA), more preferably 0 to 10% by mass.

[0128] <<Phenoxy Resin (B)>>

[0129] The composition of the present invention contains a phenoxy resin (B) with a Tg exceeding 120°C in the uncured state, as determined by differential scanning calorimetry (DSC).

[0130] The composition of the present invention contains phenoxy resin (B), which has excellent non-stickiness, adhesive properties and toughness.

[0131] It should be noted that resins formed by increasing the molecular weight of low-molecular-weight epoxy compounds are traditionally called phenoxy resins. The phenoxy resin (B) described above does not contain the epoxy resin (AA). Furthermore, the phenoxy resin (B) described above does not contain the toughening agent (D) described later.

[0132] Specific examples of phenoxy resins (B)

[0133] Examples of phenoxy resins (B) include phosphorus-containing phenoxy resins (B1), fluorene-containing phenoxy resins (B2), phenoxy resins with a bisphenol backbone, phenoxy resins with a phenolic varnish backbone, phenoxy resins with a naphthalene backbone, and phenoxy resins with a biphenyl backbone.

[0134] From the viewpoint that the effects of the present invention (especially the toughness) are superior, the phenoxy resin (B) preferably contains at least one selected from the group consisting of phosphorus-containing phenoxy resin (B1), fluorene-containing phenoxy resin (B2), and phenoxy resin containing a bisphenol S backbone (B3). In addition to the above, from the viewpoint that the heat resistance and adhesion to the electromagnetic steel sheet are superior, it is more preferable to contain phenoxy resin (B3) containing a bisphenol S backbone.

[0135] <Phosphorus-containing phenoxy resin (B1)>

[0136] Phosphorus-containing phenoxy resin (B1) is a phenoxy resin containing phosphorus.

[0137] From the viewpoint that the present invention has superior effects, the phosphorus-containing phenoxy resin (B1) preferably has the skeleton shown in the following formula (B1-1).

[0138]

[0139] In equation (B1-1), R 1 Each can independently represent a hydrogen atom or a methyl group, and m and n can each be 1 or more. m+n can be set to the weight-average molecular weight value corresponding to the phenoxy resin (B) described later.

[0140] <Fluorene-containing phenoxy resin (B2)>

[0141] Fluorene-containing phenoxy resin (B2) is a phenoxy resin containing fluorene.

[0142] From the viewpoint that the present invention has superior effects, the fluorene-containing phenoxy resin (B2) preferably has the skeleton shown in the following formula (B2-1).

[0143]

[0144] In equation (B2-1), R 1 Each can independently represent a hydrogen atom or a methyl group, and p and q can each independently be 1 or more. p+q can be set to the weight-average molecular weight value corresponding to the phenoxy resin (B) described later.

[0145] <Phenoxy resins containing a bisphenol S backbone (B3)>

[0146] The phenoxy resin containing the bisphenol S backbone (B3) is a phenoxy resin with a bisphenol S backbone.

[0147] From the viewpoint that the present invention has superior effects, the phenoxy resin (B3) containing the bisphenol S backbone preferably has the backbone shown in the following formula (B3-1).

[0148]

[0149] In formula (B3-1), R 1 Each of them independently represents a hydrogen atom or a methyl group, and r and s are each independently 1 or more. r+s can be set to the weight-average molecular weight value corresponding to the phenoxy resin (B) described later.

[0150] It should be noted that there are no particular restrictions on the ends of the structures in formulas (B1-1), (B2-1), and (B3-1). For example, epoxy groups or hydrogen atoms can be bonded to these ends. When epoxy groups are bonded to the ends, the ends and epoxy groups can be bonded by linking groups. There are no particular restrictions on the linking groups.

[0151] <Glass transition temperature of phenoxy resin (B)>

[0152] In the composition of the present invention, the glass transition temperature (Tg) of the uncured phenoxy resin (B) obtained by differential scanning calorimetry (DSC) exceeds 120°C.

[0153] "Phenoxy resin (B) in its uncured state" refers to phenoxy resin (B) in its state before being mixed with the composition of the present invention.

[0154] Because the Tg of the phenoxy resin (B) contained in the composition of the present invention is within the above-mentioned range, the adhesive cured product obtained from the composition of the present invention has excellent toughness and excellent adhesive properties.

[0155] For the glass transition temperature of phenoxy resin (B), a differential scanning calorimeter (DSC-50) manufactured by SHIMADZU was used to measure the DSC curve over the temperature range of 50°C to 370°C by heating at a rate of 15°C / min until reaching 370°C. The temperature at the initial inflection point of the above DSC curve was set as the glass transition temperature of phenoxy resin (B).

[0156] From the viewpoint that the effect of the present invention is superior when the phenoxy resin (B) has epoxy groups, the epoxy equivalent of the phenoxy resin (B) is preferably 5000 g / eq or more. The epoxy resin (A) and phenoxy resin (B) molecules are chemically bonded, and even if phase separation occurs within the cured resin, the interfacial strength is easily ensured while maintaining toughness.

[0157] Phenoxy resins (B) may not have epoxy groups.

[0158] • Weight-average molecular weight of phenoxy resin (B)

[0159] From the viewpoint of achieving superior results according to the present invention, the weight-average molecular weight of the phenoxy resin (B) is preferably 30,000 to 500,000, more preferably 35,000 to 100,000. A weight-average molecular weight less than 30,000 does not result in sufficient toughness, while a weight-average molecular weight exceeding 100,000 may increase the viscosity of the adhesive liquid, making uniform coating of the steel plate difficult.

[0160] In this invention, the weight-average molecular weight (Mw) of the phenoxy resin can be set as the equivalent value of standard polystyrene determined by gel permeation chromatography (GPC) using tetrahydrofuran as a solvent.

[0161] The weight-average molecular weight (Mw) of phenoxy resins can also be a catalog value.

[0162] <Content of phenoxy resin (B)>

[0163] In the composition of the present invention, the content of phenoxy resin (B) is 20 to 80 parts by mass relative to 100 parts by mass of the total amount of epoxy resin (AA). If the content of phenoxy resin (B) is less than 20 parts by mass, the toughness of the cured adhesive may be insufficient. Furthermore, if the content of phenoxy resin (B) exceeds 80 parts by mass, the Tg of the cured adhesive cannot exceed 160°C.

[0164] <Amine-based latent curing agent (C)>

[0165] The compositions of the present invention contain an amine-based latent curing agent (C).

[0166] Several methods are known for curing epoxy resins. While anhydride and phenolic curing agents improve bond strength, their slow curing speed makes them unsuitable for this invention. Furthermore, conventional polyamine curing agents are unsuitable for this invention due to their excessively rapid curing.

[0167] The composition of the present invention contains an amine-based latent curing agent (C), and the effects of the present invention (especially the adhesive properties after long-term storage) are excellent.

[0168] In this invention, a latent curing agent refers to a curing agent that can begin to react by heating or the like. Latent curing agents differ from conventional curing agents that react at room temperature (e.g., 25°C); they do not react at room temperature, or if they do, the reaction is very minimal.

[0169] The amine-based latent curing agent (C) has nitrogen atoms and can function as a curing agent for epoxy resin (AA) and / or phenoxy resin (B). It should be noted that in this invention, the phenoxy resin (B) does not have epoxy groups, or even if it does, the Mw of the phenoxy resin (B) is greater than that of the epoxy resin (AA). Therefore, it is assumed that the majority of the amine-based latent curing agent (C) reacts with the epoxy resin (AA).

[0170] Specific examples of amine-based latent curing agents (C)

[0171] Examples of amine-based latent curing agents (C) include dicyandiamide, modified polyamines, acylhydrazides, urea compounds such as 4,4'-diaminodiphenyl sulfone (DDS), DCMU: 3-(3,4-dichlorophenyl)-1,1-dimethylurea, imidazole compounds such as 2-ethyl-4-methylimidazolium, and melamine. These can be used alone or in combination of two or more.

[0172] From the viewpoint that the present invention has superior effects, the amine-based latent curing agent (C) preferably contains at least one selected from the group consisting of dicyandiamide, urea, 4,4'-diaminodiphenyl sulfone and imidazole compounds.

[0173] More preferably, it contains a combination of dicyandiamide and urea and / or imidazole compounds, or 4,4'-diaminodiphenyl sulfone (4,4'-diaminodiphenyl sulfone can be used alone).

[0174] Further preferred combinations are dicyandiamide and 3-(3,4-dichlorophenyl)-1,1-dimethylurea, or 4,4'-diaminodiphenyl sulfone.

[0175] • Content of amine-based latent curing agent (C)

[0176] From the viewpoint that the effects of the present invention are superior, the content of the amine-based latent curing agent (C) (when the amine-based latent curing agent (C) contains multiple amine-based latent curing agents (C), it is the total content of the above-mentioned multiple amine-based latent curing agents (C)) is preferably 5 to 70 parts by weight relative to 100 parts by weight of epoxy resin (AA).

[0177] When the amine-based latent curing agent (C) contains dicyandiamide and urea, the total content of the amine-based latent curing agent (C) is preferably 5 to 20 parts by weight relative to 100 parts by weight of epoxy resin (AA).

[0178] When the amine-based latent curing agent (C) contains 4,4'-diaminodiphenyl sulfone, the content of the amine-based latent curing agent (C) is preferably 25 to 50 parts by weight relative to 100 parts by weight of epoxy resin (AA).

[0179] • Toughening agent (D)

[0180] From the viewpoint that the resulting cured adhesive has superior toughness, the composition of the present invention preferably further contains a toughening agent (D).

[0181] Toughening agents (D) refer to compounds that can further impart toughness to the resulting cured adhesive.

[0182] The toughening agent (D) is preferably made of a polymer with flexibility.

[0183] Examples of toughening agents (D) include core-shell type, rubber-modified epoxy resin, and urethane-modified epoxy resin.

[0184] It should be noted that toughening agent (D) is not present in the above-mentioned epoxy resin (AA), phenoxy resin (B), and amine-based latent curing agent (C).

[0185] The toughening agent (D) may or may not react with the aforementioned amine-based latent curing agent (C), epoxy resin (AA), or phenoxy resin (B).

[0186] From the viewpoint that the effects (especially toughness) of the present invention are superior, the toughening agent (D) preferably contains at least one selected from the group consisting of core-shell type, rubber modified epoxy resin and urethane modified epoxy resin, more preferably contains a core-shell type toughening agent, and even more preferably contains a core-shell type toughening agent (D1) with an average particle size of 0.05 to 0.2 μm.

[0187] Core-shell toughening agents

[0188] One example of a preferred method is that core-shell toughening agents are in granular form.

[0189] Core-shell toughening agents have a core layer and a shell layer.

[0190] Examples of core-shell toughening agents include two-layer rubber particles with an outer shell made of a glassy polymer and an inner core made of a rubbery polymer, and three-layer rubber particles with an outer shell made of a glassy polymer, an intermediate layer made of a rubbery polymer, and a core made of a glassy polymer. The glassy polymer can be, for example, a polymer of (meth)acrylate and / or a polymer of styrene. The rubbery polymer layer can be, for example, a polymer of butyl acrylate (butyl rubber), silicone rubber, or polybutadiene.

[0191] • Average particle size of toughening agent (D)

[0192] Considering the superior toughness of the resulting cured adhesive and the fact that it does not reduce Tg, the average particle size of the toughening agent (D) is preferably 0.005 μm or more and 0.6 μm or less, more preferably 0.05 μm or more and 0.2 μm or less. When the particle size is less than 0.005 μm, the dispersion of the particles in the epoxy resin deteriorates, and when it exceeds 0.6 μm, the heat resistance may deteriorate.

[0193] The average particle size of the toughening agent (D) refers to the particle size at the cumulative 50% (50% volume cumulative diameter) obtained by measuring the particle size distribution on a volume basis using a laser diffraction particle size distribution measuring device. Examples of laser diffraction particle size distribution measuring devices include, for instance, the "Microtrac MT3000II series" laser diffraction scattering particle size distribution measuring device manufactured by MicrotracBEL Corp.

[0194] The same applies to the average particle size of the core-shell toughening agent (D) mentioned above.

[0195] Rubber-modified epoxy resin

[0196] Rubber-modified epoxy resin is an epoxy resin with two or more epoxy groups and a rubber backbone.

[0197] Examples of rubbers that form the aforementioned skeleton include polybutadiene and acrylonitrile butadiene rubber (NBR).

[0198] From the viewpoint that the present invention has superior effects, the epoxy equivalent of the rubber-modified epoxy resin is preferably 200 g / eq or more and 500 g / eq or less.

[0199] · Carbamate-modified epoxy resin

[0200] The urethane-modified epoxy resin is an epoxy resin with two or more epoxy groups and a polyurethane backbone.

[0201] There are no particular restrictions on the polyurethane forming the above-mentioned skeleton if it is a polymer having multiple urethane bonds and / or urea bonds.

[0202] From the viewpoint that the present invention has superior effects, the epoxy equivalent of the urethane-modified epoxy resin is preferably 200 g / eq or more and 500 g / eq or less.

[0203] • Content of toughening agent (D)

[0204] When the composition of the present invention further contains a toughening agent (D), the content of the toughening agent (D) (or the total content of two or more toughening agents (D)) relative to 100 parts by weight of epoxy resin (AA) is preferably 1 to 30 parts by weight, more preferably 5 to 20 parts by weight. A content less than 1 part by weight or more than 30 parts by weight is insufficient to exhibit a toughening effect and results in poor heat resistance, respectively.

[0205] (additive)

[0206] The compositions of the present invention may further contain various additives as needed within the scope of achieving the effects of the present invention. Examples of additives include, for instance, fillers, reaction retarders, anti-aging agents, antioxidants, pigments, dyes, plasticizers, silane coupling agents, thixotropic agents, thickeners, flame retardants, antistatic agents, ultraviolet absorbers, surfactants, dispersants, dehydrating agents, and solvents.

[0207] Solvent

[0208] Examples of solvents include ketone solvents such as acetone, methyl ethyl ketone (MEK), and cyclohexanone; ester solvents such as ethyl acetate and butyl acetate; aliphatic solvents such as n-hexane; alicyclic solvents such as cyclohexane; and aromatic solvents such as toluene, xylene, and cellosol esters.

[0209] The amount of solvent is preferably 80 to 300 parts by weight relative to 100 parts by weight of the epoxy resin (AA). If it is less than 80 parts by weight, it will thicken and be difficult to coat evenly; if it is more than 300 parts by weight, it will be difficult to coat the adhesive layer with good thickness accuracy on the steel plate surface.

[0210] The method of manufacturing the composition of the present invention is not particularly limited. For example, it can be obtained by mixing the above-mentioned epoxy resin (A), phenoxy resin (B), amine latent curing agent (C), other epoxy compounds, toughening agent (D) and various additives as needed, using a mixer or other stirrer.

[0211] The compositions of the present invention can be used as adhesive compositions for laminating electromagnetic steel sheets.

[0212] The compositions of the present invention can be cured, for example, at 140–250°C. The curing temperature is preferably above the activation temperature of the amine-based latent curing agent (C). Pressure can be applied during the curing process described above.

[0213] The composition of the present invention, after curing, becomes the "cured adhesive obtained from the composition of the present invention" as described above, or the adhesive layer of the iron core formed using the composition of the present invention as described later.

[0214] <Glass transition temperature of cured adhesive>

[0215] In this invention, the glass transition temperature of the cured adhesive (or adhesive layer, hereinafter the same) obtained from the composition of this invention exceeds 160°C based on differential scanning calorimetry.

[0216] With a glass transition temperature exceeding 160°C due to the adhesive curing process, the compositions of the present invention exhibit excellent toughness even at high temperatures.

[0217] From the viewpoint that the present invention has superior effects, the glass transition temperature of the cured adhesive is preferably 180°C or higher, more preferably 200-280°C.

[0218] Methods for determining the glass transition temperature of cured adhesives

[0219] For the glass transition temperature of the cured adhesive, a differential scanning calorimeter (DSC-50) manufactured by SHIMADZU was used to measure the DSC curve over the temperature range of 50°C to 370°C by heating at a rate of 15°C / min until reaching 370°C.

[0220] In this invention, the temperature of the initial inflection point of the DSC curve is essentially set as the glass transition temperature of the adhesive cured product (adhesive layer).

[0221] In addition, when the adhesive cured product has a phase structure such as an island structure or a co-continuous phase structure, the DSC curve shows that, based on the glass transition temperatures of various resins that form the above-mentioned phase structure, the glass transition temperature of the resin contained in the adhesive cured product in large quantity, or (not regionally) the glass transition temperature of the matrix resin, is set as the glass transition temperature of the adhesive cured product (adhesive layer).

[0222] It should be noted that in this invention, the content of epoxy resin (AA) is greater than that of phenoxy resin (B). Therefore, in the obtained cured adhesive, the content of epoxy resin (AA) and amine-based latent curing agent (C) is significantly more dominant than that of phenoxy resin (B).

[0223] <Yield stress at 25℃ ≥60MPa>

[0224] From the viewpoint that the cured adhesive obtained by curing the composition of the present invention has better effects (especially toughness) and the core is not easily damaged or deformed even when the core rotates at high speed, the yield stress measured at 25°C is preferably 60 MPa or more, more preferably 80 to 200 MPa.

[0225] <Yield stress at 140℃ ≥20MPa>

[0226] From the viewpoint that the cured adhesive obtained by curing the composition of the present invention has better effects (especially toughness) and that the core is not easily damaged or deformed even when the core is rotated at high speed under high temperature conditions, the yield stress measured at 140°C is preferably 20 MPa or more, more preferably 35 MPa or more.

[0227] Previously, the temperature of a rotor with embedded permanent magnets during continuous rotation, without cooling by engine oil or similar means, was reportedly raised to around 140°C (Reference: Hirano Satoru, "Thermal Flow Characteristics of a Rotating Double Cylinder Simulated in an Electric Vehicle Motor Structure", p. 9, 2013, Graduate Thesis No. 12102-A 6725, University of Tsukuba). Therefore, since the yield stress of the cured adhesive, measured at 140°C, is 20 MPa or higher, the strength (toughness) of the cured adhesive can be sufficiently maintained even under high-temperature conditions without cooling by engine oil or similar means. It is believed that applying the composition of the present invention to a laminated core can suppress deformation and damage during high-speed rotation of the aforementioned laminated core.

[0228] The cured adhesive product preferably has a yield stress of 60 MPa or more when measured at 25°C and 20 MPa or more when measured at 140°C, in accordance with JIS K7161. More preferably, the yield stress is 85 MPa or more when measured at 25°C and 35 MPa or more when measured at 140°C.

[0229] In this invention, the yield stress (tensile yield stress) of the cured adhesive obtained by curing the composition of this invention at 25°C was measured according to JIS K 7161:2014 at 25°C. Furthermore, the yield stress of the cured adhesive obtained by curing the above-mentioned adhesive at 140°C was measured according to JIS K 7161:2014 at 140°C.

[0230] [core]

[0231] For the iron core formed using the composition of the present invention, electromagnetic steel plates and adhesive layers are alternately stacked, and the adhesive layers are formed using the electromagnetic steel plate stacking adhesive composition of the present invention.

[0232] This core, suitable for the present invention, is formed using the composition of the present invention through an adhesive layer, exhibiting excellent bonding properties and superior toughness over a wide temperature range. Therefore, it is believed that this core is not easily damaged or deformed even when rotating at high speeds under a wide range of temperature conditions, including high temperatures.

[0233] If the adhesive composition for laminating electromagnetic steel plates used in the core is the adhesive composition for laminating electromagnetic steel plates of the present invention (in the core formed using the composition of the present invention, it is simply referred to as the "composition"), there is no particular limitation.

[0234] Furthermore, there are no particular limitations on the electromagnetic steel sheet used in the core formed using the composition of the present invention. Examples of conventionally known electromagnetic steel sheets can be cited.

[0235] The aforementioned adhesive layer preferably has a yield stress of 60 MPa or more when measured at 25°C, according to JIS K7161, and a yield stress of 20 MPa or more when measured at 140°C.

[0236] The yield stress of the adhesive layer in the iron core formed using the composition of the present invention is the same as the yield stress of the cured adhesive obtained by curing the composition of the present invention.

[0237] (Adhesive force on electromagnetic steel sheet)

[0238] The adhesive of the present invention has a preferred adhesion strength to the electromagnetic steel plate, which is a shear strength of 7.0 MPa or more according to JIS K6850 at 25°C and / or 140°C.

[0239] (Manufacturing method)

[0240] The method for manufacturing an iron core using the composition of the present invention is not particularly limited if the composition of the present invention is used. Examples of manufacturing methods include those comprising the following steps:

[0241] The coating process of applying the above composition to an electromagnetic steel sheet;

[0242] A punching process for punching the electromagnetic steel sheet obtained in the coating process;

[0243] The stacking process involves layering the punched electromagnetic steel sheets after the punching process; and

[0244] A curing process that involves heating the laminate obtained in the lamination process to integrate the laminate into a single unit.

[0245] Coating process

[0246] The coating process is the process of applying the composition of the present invention to the electromagnetic steel plate.

[0247] There are no particular limitations on the method of coating the above composition onto the electromagnetic steel sheet. Examples include, for instance, roller coating, gravure coating, air blade coating, doctor blade coating, squeegee coating, bar coating, kiss coating, droplet coating, cast coating, rotary screen coating, slit coating, spray coating, inkjet coating, spin coating, and electrodeposition coating.

[0248] In the coating process, the above composition can be applied to at least one side of the electromagnetic steel sheet.

[0249] • Thickness of the coated composition

[0250] After the coating process, the thickness of the above composition after coating and drying, taking into account the unevenness of the electromagnetic steel sheet and the ease of pressing the electromagnetic steel sheet, is preferably 1 to 20 μm, and particularly preferably 2 to 10 μm.

[0251] Drying process

[0252] When the composition used in the core formed using the composition of the present invention contains a solvent, it is preferable to perform a drying process after coating to remove the solvent from the above-mentioned composition. After the drying process (or after the above-mentioned coating process if there is no drying process), a composite material made by applying the composition of the present invention to an electromagnetic steel sheet can be obtained.

[0253] Drying methods in the drying process include, for example, hot air drying, induction heating, and vacuum heating.

[0254] Preferably, the mixture is dried until it reaches a state where the composition formed on the electromagnetic steel plate does not stick together (so-called non-stick).

[0255] There is no particular temperature limit during the drying process. If the epoxy resin reacts excessively, the adhesion will be insufficient during curing. On the other hand, if no reaction occurs at all, the epoxy resin will become sticky, leading to the problem of steel plates sticking together. Furthermore, to improve the productivity of the coating and drying processes, it is preferable to perform drying at a relatively high temperature for a short time. Specifically, drying at 150°C or above for several seconds to tens of seconds is preferred.

[0256] The composite material obtained as described above can be stored, for example, in a rolled or sheet-like state, or in an overlapping state. Because the adhesive layer of the composite material exhibits excellent non-adhesiveness, the adhesive layer will not peel off from the composite material when it is unrolled for use.

[0257] • Punching process

[0258] The blanking process is the process of blanking the aforementioned composite material. Examples of methods for blanking the composite material include shearing. There are no particular limitations on the shape of the blanked composite material.

[0259] •Lamination process

[0260] The lamination process is the process of stacking the blanked composite material from the above-mentioned blanking process.

[0261] There is no particular limitation on the number of sheets of the aforementioned composite material used in the lamination.

[0262] The above-mentioned composite material can be stacked by alternately stacking electromagnetic steel plates and the above-mentioned composition.

[0263] Curing process

[0264] The curing process is a process of heating the laminate obtained in the lamination process to integrate the laminate into a single unit.

[0265] The preferred heating temperature during the curing process is 130–300°C.

[0266] When pressure is applied during the curing process, the pressure is preferably 0.1 to 10 MPa.

[0267] There are no particular restrictions on the methods of heating and pressurizing during the curing process.

[0268] After the curing process, an iron core formed using the composition of the present invention can be obtained.

[0269] Example

[0270] The present invention will be described below through examples. The present invention is not limited to the examples.

[0271] Electromagnetic steel sheet

[0272] Non-directional electromagnetic steel plates with a thickness of 0.15 mm and a yield strength of 200-550 MPa are used.

[0273] [Adhesive composition for laminating electromagnetic steel sheets]

[0274] Each composition is prepared by mixing the components shown in Table 1 below (parts by mass) at 25°C.

[0275] It should be noted that the amounts of phenoxy resin (B) and YP-50 shown in Table 1 are net weight amounts of phenoxy resin. The amount of toughening agent (D) is net weight amount of toughening agent.

[0276] The detailed descriptions of each component shown in Table 1 are as follows.

[0277] (Epoxy resin with 3 or more functionalities (A))

[0278] (Solid epoxy resin)

[0279] Phenolic varnish-type epoxy resin: A phenolic varnish-type epoxy resin with 7 epoxy groups per molecule. Epoxy equivalent 190 g / eq. Trade name EPPN201, manufactured by Nippon Kayaku Co., Ltd. Softening temperature 65–78°C. Solid at room temperature (25°C).

[0280] • Cresol-phenolic varnish-type epoxy resin: A cresol-phenolic varnish-type epoxy resin with 3 to 10 epoxy groups per molecule. Epoxy equivalent 209 g / eq. Trade name: YDCN-704A, manufactured by NIPPON STEEL Chemical & Material Co., Ltd. Softening temperature: 87–93°C. Solid at room temperature (25°C).

[0281] (Nitrogen-containing epoxy resin)

[0282] • Nitrogen-containing epoxy resin (1): The trifunctional epoxy resin shown in formula (1) below. Epoxy equivalent 97 g / eq.

[0283] Product name EP-3950E, manufactured by ADEKA. Liquid at room temperature (25°C).

[0284]

[0285] • Nitrogen-containing epoxy resin (2): The tetrafunctional epoxy resin shown in formula (2) below. Epoxy equivalent 110 g / eq. Trade name YH404, manufactured by NIPPON STEEL Chemical & Material Co., Ltd. Liquid at room temperature (25°C).

[0286]

[0287] (Epoxy resins other than epoxy resin (A))

[0288] • Bisphenol A type epoxy resin: Bisphenol A type epoxy resin. 2-functional. Molecular weight 380, epoxy equivalent 190±5 g / eq, Epikote 828, manufactured by Mitsubishi Chemical Corporation. Liquid at room temperature (25℃).

[0289] (Phenoxy resins with a Tg exceeding 120℃ (B))

[0290] YPS-007: A phenoxy resin with a bisphenol S backbone. Manufactured by NIPPON STEEL Chemical & Material Co., Ltd. Tg in the uncured state exceeds 120°C. Mw is above 40,000 and below 100,000.

[0291] • ERF-001: Phosphorus-containing phenoxy resin. Manufactured by NIPPON STEEL Chemical & Material Co., Ltd. Uncured Tg exceeds 120°C. Mw is above 40,000 and below 100,000.

[0292] • F-Resin: A fluorene-containing phenoxy resin manufactured as follows. Tg in the uncured state exceeds 120°C. Mw is 40,000 or higher and 100,000 or lower.

[0293] …Preparation of F-Resin

[0294] In a mixed solvent of cyclohexanone and toluene, 1.02 mol of bisphenol A glycidyl ether and 1.0 mol of 9,9-bis(4-hydroxyphenyl)fluorene (the structure below) were reacted at a temperature of 150°C to 170°C for 8 hours in the presence of a catalyst amount of 2-ethyl-4-methylimidazole (manufactured by Shikoku Chemical Industry Co., Ltd., 2E4MZ) to obtain a solution containing 40% by mass of a fluorene-containing phenoxy resin based on solids.

[0295]

[0296] The resulting fluorene-containing phenoxy resin is called "F-Resin". The structure of F-Resin is represented by the following formula (B2-2).

[0297]

[0298] (B2-2)

[0299] In equation (B2-2), R 1 denoted by methyl groups, p and q are each independently 1 or more, and p+q is the value corresponding to the above weight-average molecular weight.

[0300] • (Comparison) YP-50: Bisphenol A type phenoxy resin with a Tg of 84℃. Trade name YP-50, manufactured by NIPPON STEELC Chemical & Material Co., Ltd., Tg 84℃, Mw is 60000~70000 (catalog value).

[0301] (Toughening agent (D))

[0302] • Kane Ace MX-154 (Core-shell toughening agent (D1)): A mixture containing core-shell rubber particles at a ratio of 33% by mass. The core-shell rubber particles function as a toughening agent. Trade name: Kane Ace MX-154; manufactured by KANEKACORPORATION. It should be noted that the values ​​shown in the Kane Ace MX-154 column represent the net weight of the core-shell rubber particles in Kane Ace MX-154. Average particle size: 0.1 μm.

[0303] • EPR-21 (Rubber-Modified Epoxy): Rubber-modified epoxy resin. Trade name: EPR-21, manufactured by ADEKA. Epoxy equivalent: 200 g / eq.

[0304] (Amine-based latent curing agent (C))

[0305] • Dicyandiamide: EH-3636AS manufactured by ADEKA

[0306] ·DCMU: 3-(3,4-dichlorophenyl)-1,1-dimethylurea, manufactured by Hodogaya UPL Co., Ltd.

[0307] • DDS: 4,4'-Diaminodiphenyl sulfone, manufactured by Wakayama Seika Kogyo Co., Ltd.

[0308] (solvent)

[0309] Cyclohexanone

[0310] (Evaluation of cured adhesive products)

[0311] • Determination of glass transition temperature (Tg)

[0312] Each composition prepared as described above was cast onto a release film to form a thickness of 200 μm, cured in an oven at 150°C for 1 hour, and the glass transition temperature of the resulting cured adhesive was determined by differential scanning calorimetry (DMC measurement, heating rate 10°C / min).

[0313] The results are shown in the "Glass transition temperature of adhesive cured product" column of Table 1.

[0314] Evaluation Criteria

[0315] In this invention, the Tg of the cured adhesive exceeds 160°C.

[0316] (Evaluation of cured adhesive: toughness)

[0317] Tensile test specimens of each composition as described above were prepared using the following method in accordance with JIS K 7161 (2014).

[0318] • Preparation of tensile test pieces

[0319] Tensile test pieces were prepared according to JIS K 7161 (2014) using the compositions manufactured as described above. First, the compositions manufactured as described above were cast onto a release film to a thickness of 100 μm, and then vacuum degassed for 3 days. The resulting film was then cured in an oven at 150°C for 1 hour. The resulting cured adhesive was then cut into No. 1 dumbbell shapes to form tensile test pieces.

[0320] Tensile test

[0321] Using the tensile test specimens prepared as described above, the yield stress of the cured adhesive (adhesive layer) obtained from the composition of the present invention was measured according to JIS K 7161:2014 using a universal testing machine with a temperature control system, model 5966 (manufactured by Instron Limited), at 25°C or 140°C and 50%RH ± 5%RH. The yield strength of five tensile test specimens was measured at a tensile speed of 5 mm / min, a mark spacing of 20 mm (using a contact elongation meter), and a chuck spacing of 40 mm, and the average value was calculated.

[0322] The yield strength (average value) at 25°C is shown in the “Toughness at room temperature (stress / MPa@25°C)” column of Table 1.

[0323] The yield strength (average value) at 140℃ is shown in the "Toughness at High Temperature (Stress / MPa@140℃)" column of Table 1.

[0324] • Evaluation criteria for resilience

[0325] When the yield stress at 25°C (evaluation of toughness at room temperature) is above 60 MPa and the yield stress at 140°C (evaluation of toughness under high temperature conditions) is above 20 MPa, it is evaluated that the toughness is excellent not only at room temperature but also under high temperature conditions.

[0326] If the yield stress at 25℃ is less than 60MPa, or the yield stress at 140℃ is less than 20MPa, it is evaluated as having poor toughness.

[0327] (The non-sticky nature of the composition after drying)

[0328] Evaluation methods for non-viscous properties

[0329] Each composition manufactured as described above is cast onto an electromagnetic steel plate with a thickness of 20 μm and kept in an oven at 130°C for 30 minutes to dry the solvent in each composition.

[0330] The results are shown in the "Non-sticky after drying" column of Table 1.

[0331] Evaluation criteria for non-viscous properties

[0332] If the dried composition does not feel sticky when touched with a finger, it is rated as having excellent non-stickiness and is indicated by "○".

[0333] If the dried composition feels sticky when touched with a finger, but does not peel off from the electromagnetic plate when the finger is pressed against the dried composition and then separated, it is evaluated as having slightly better non-stickiness, and is indicated by "△".

[0334] If the dried composition feels sticky when touched with a finger, and the dried composition peels off from the electromagnetic steel plate when the finger is separated, it is evaluated as having poor non-stickiness and is marked as "×".

[0335] (Evaluation of cured adhesive: shear strength)

[0336] • Shear strength (initial stage)

[0337] Prepare two electromagnetic steel sheets. Cast the compositions manufactured as described above onto the first electromagnetic steel sheet with a thickness of 6 μm. Keep the mixture in an oven at 130°C for 10 minutes to dry the solvent in each composition.

[0338] The dried composition on the above-mentioned electromagnetic steel plate is laminated with another electromagnetic steel plate to form a laminate, and the laminate is cured in an oven at 160°C for 1 hour to obtain a test piece.

[0339] Using the test specimens described above, the initial shear strength was determined at 140℃ according to JIS K 6850. The results are shown in the "Shear Strength (Initial) / MPa@140℃" column of Table 1.

[0340] • Shear strength (6 months at 40℃)

[0341] Prepare two electromagnetic steel sheets. On the first electromagnetic steel sheet, cast each composition manufactured as described above with a thickness of 6 μm. Keep it in an oven at 130°C for 10 minutes to dry the solvent in each composition. Then, store the electromagnetic steel sheet with the dried composition in an oven at 40°C for 6 months.

[0342] After being stored for 6 months, the composition on the electromagnetic steel plate was laminated with another electromagnetic steel plate to form a laminate, and the laminate was cured in an oven at 150°C for 1 hour to obtain a test piece.

[0343] Using the test specimens described above, the shear strength was determined at 140℃ according to JIS K 6850. The results are shown in the "Shear Strength (40℃ for 6 months) / MPa@140℃" column of Table 1.

[0344] • Evaluation criteria for the reduction in bond strength after long-term storage

[0345] When both the initial shear strength and the shear strength after 6 months of storage are above 7.0 MPa, it is evaluated that the bond strength can be suppressed after long-term storage.

[0346] If the initial shear strength is above 7.0 MPa, but the shear strength after 6 months of storage is less than 7.0 MPa, it is evaluated as failing to suppress the decrease in bond strength after long-term storage.

[0347] When the initial shear strength is less than 7.0 MPa, the bond strength is evaluated as low under the initial high temperature conditions.

[0348] [Table 1]

[0349]

[0350] As shown in Table 1, Comparative Example 1, which had a phenoxy resin (B) content less than the specified range, exhibited poor toughness and poor non-stickiness at room temperature.

[0351] Comparative Example 2, in which the content of phenoxy resin (B) exceeded the specified range, resulted in an adhesive curing product with a low glass transition temperature, poor toughness under high temperature conditions, and low bond strength before and after long-term storage.

[0352] Comparative Examples 3 and 5, which do not contain phenoxy resin (B) but instead contain phenoxy resin in its uncured state with a glass transition temperature of 120°C or lower, have adhesives with cured products that have a glass transition temperature that is not low, but exhibit significantly reduced toughness under high temperature conditions and low bond strength under high temperature conditions before and after long-term storage.

[0353] Comparative Example 4, which does not contain the specified epoxy resin (A) and instead contains a difunctional epoxy resin, produces an adhesive with a low glass transition temperature, poor toughness at room temperature or high temperature, poor non-adhesiveness, and low bond strength before and after long-term storage.

[0354] On the other hand, the composition of the present invention has excellent non-stick properties until the production of the laminated electromagnetic steel sheet, excellent adhesive properties even after long-term storage, and the resulting cured adhesive exhibits excellent toughness over a wide temperature range.

[0355] Based on the above results, it is concluded that the iron core formed using the composition of the present invention has an adhesive layer formed by the composition of the present invention, which has excellent adhesive properties and excellent toughness over a wide temperature range. Therefore, even if the iron core formed using the composition of the present invention is rotated at high speed under a wide temperature range, including high temperature, it is not easily damaged or deformed.

[0356] The application claims priority based on Japanese Special Application No. 2021-102360 filed on June 21, 2021, and incorporates all of its disclosure herein.

Claims

1. An adhesive composition for laminating electromagnetic steel sheets, comprising: an epoxy resin (AA) containing an epoxy resin (A) having three or more epoxy groups in one molecule. Phthaloresin (B) with a glass transition temperature exceeding 120°C in the uncured state, determined by differential scanning calorimetry, and Amine-based latent curing agent (C), The epoxy resin (A) contains an epoxy resin with a softening temperature of 60°C or higher. The content of the phenoxy resin (B) is 20 to 80 parts by weight relative to 100 parts by weight of the epoxy resin (AA). The glass transition temperature of the obtained cured adhesive, determined by differential scanning calorimetry, exceeded 160°C. The phenoxy resin (B) contains at least one selected from the group consisting of phosphorus-containing phenoxy resin (B1), fluorene-containing phenoxy resin (B2), and phenoxy resin containing a bisphenol S backbone (B3). The epoxy resin with a softening temperature of 60°C or higher contains phenolic varnish-type epoxy resin (A1) and / or cresol varnish-type epoxy resin (A2). The epoxy resin (A) further contains an epoxy resin having N,N-diglycidylamino groups, wherein the content of the epoxy resin having N,N-diglycidylamino groups is less than 50% by mass of the total amount of the epoxy resin (AA).

2. The adhesive composition for laminating electromagnetic steel sheets according to claim 1, wherein, The content of the epoxy resin with a softening temperature of 60°C or higher is 50% by mass or higher of the total amount of epoxy resin (AA).

3. The adhesive composition for laminating electromagnetic steel sheets according to claim 1 or 2, wherein, The epoxy resin having N,N-diglycidylamino groups contains epoxy resin (A3) as shown in formula (1) and / or epoxy resin (A4) as shown in formula (2). 。 4. The adhesive composition for laminating electromagnetic steel sheets according to claim 1 or 2, wherein, The content of the amine-based latent curing agent (C) is 5 to 70 parts by weight relative to 100 parts by weight of the epoxy resin (AA).

5. The adhesive composition for laminating electromagnetic steel sheets according to claim 1 or 2, further comprising a toughening agent (D).

6. The adhesive composition for laminating electromagnetic steel sheets according to claim 5, wherein, The toughening agent (D) has an average particle size of 0.005~0.6μm and contains a core-shell type toughening agent (D1).

7. The adhesive composition for laminating electromagnetic steel sheets according to claim 5, wherein, The toughening agent (D) content is 1 to 30 parts by weight relative to 100 parts by weight of the epoxy resin (AA).

8. The adhesive composition for laminating electromagnetic steel sheets according to claim 1 or 2, wherein, The content of the 2-functional epoxy resin is 0 to 40% by mass of the epoxy resin (AA).

9. The adhesive composition for laminating electromagnetic steel sheets according to claim 1 or 2, wherein, The cured adhesive, according to JIS K7161, has a yield stress of 60 MPa or more at 25°C and a yield stress of 20 MPa or more at 140°C.

Citation Information

Patent Citations

  • Laminated silicon steel sheet having excellent workability

    JP2002146492A

  • Motor for electric vehicle or laminated plate for generator and motor or generator

    JP2004042345A

  • Non-oriented electrical steel sheet composition, method for producing non-oriented electrical steel sheet product, and non-oriented electrical steel sheet product

    JP2016540901A

  • Annular laminated core material and manufacturing method of the same

    JP2020171171A

  • Hybrid vehicle control unit

    JP2021102360A